The repercussions of the Covid-19 pandemic and its impact on achieving cybersecurity - وفاء مطروح; ابتسام أونيس2 (International Journal of Social Communication, 2022)
At a time when the Covid-19 virus has infected nearly 200 countries around the world and the social isolation it has imposed, sometimes completely, forcing individuals, companies and institutions in these countries to adopt a pattern of communication, work and distance education based on communication technologies and the Internet; the digital space has become (Cyber) serves as an alternative to the real space, and at the same time has become an attractive environment for many information hackers to practice their favorite hobby of hacking and committing various types of cybercrime. Algeria, like other countries of the world that have been affected by the repercussions of the Corona pandemic, on the one hand, and on the other hand, knows a growing increase in the use of communication technologies, as it faces serious challenges to achieve cyber security and reduce the risks of cyber crime that knows no borders, at various levels (individuals, institutions, government ), which is what the researchers will try to study in this scientific paper.